2012
DOI: 10.1111/j.1365-2141.2012.09225.x
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic induction of adaptive immune response in multiple myeloma: sequential azacitidine and lenalidomide generate cancer testis antigen‐specific cellular immunity

Abstract: Summary Patients with multiple myeloma (MM) undergoing high dose therapy and autologous stem cell transplantation (SCT) remain at risk for disease progression. Induction of the expression of highly immunogenic cancer testis antigens (CTA) in malignant plasma cells in MM patients may trigger a protective immune response following SCT. We initiated a phase II clinical trial of the DNA hypomethylating agent, azacitidine (Aza) administered sequentially with lenalidomide (Rev) in patients with MM. Three cycles of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 41 publications
(43 reference statements)
1
31
0
1
Order By: Relevance
“…Aza therapy in patients with relapsed or refractory Hodgkin lymphoma resulted in a complete response to immune checkpoint inhibitors [63]. We have also reported that the use of Aza combined with the immune modulatory lenalidomide induced the expression of CTAs within tumor cells, and generated CTA-specific immune responses in patients with multiple myeloma [64]. Similar results were observed in a mouse model of experimental metastatic breast cancer [65].…”
Section: Epigenetic Targeting Of Tumor Cells For Immune Modulationsupporting
confidence: 55%
“…Aza therapy in patients with relapsed or refractory Hodgkin lymphoma resulted in a complete response to immune checkpoint inhibitors [63]. We have also reported that the use of Aza combined with the immune modulatory lenalidomide induced the expression of CTAs within tumor cells, and generated CTA-specific immune responses in patients with multiple myeloma [64]. Similar results were observed in a mouse model of experimental metastatic breast cancer [65].…”
Section: Epigenetic Targeting Of Tumor Cells For Immune Modulationsupporting
confidence: 55%
“…810 In MM patients, combining lenalidomide and the DNMTi azacytidine stimulated an adaptive immune response by inducing the expression of antigens. 11 DNMTi and HDACi induced MAGE-A3 expression in primary MM cells, thereby stimulating recognition by MAGE-A3 cytotoxic T lymphocytes (CTLs). 12 The HDACi valproic acid induced natural killer (NK) ligands in MM cells and potentiated NK cell-mediated lysis.…”
Section: Introductionmentioning
confidence: 99%
“…Odunsi et al [19] recently published their findings that a New York esophageal squamous cell carcinoma 1 (NY-ESO-1) targeting cancer vaccine combined with decitabine treatment resulted in enhanced immune responses in advanced platinum-resistant ovarian cancer. We have used a similar strategy utilizing the DNAMTi azacytidine (Aza) in combination with lenalidomide to increase CTA-specific immune responses to multiple myeloma in patients [20]. …”
Section: Introductionmentioning
confidence: 99%